Reproductive biology and plant systematics: The growth of a symbiotic association - Anderson, Gregory J. (2002)
Systematics and reproductive biology have been closely intertwined through botanical history because both rely on reproductive characters. We consider interconnections between systematics and reproductive biology from notable papers and reviews. In addition, a review of over 6,000 journals and millions of articles using the ISI Web of Science®demonstrates a steady growth in publication of papers on reproductive biology from 1975 to 2001. Furthermore, the rate of publications that link systematics with reproductive biology shows a steep increase from 1991 to the present. This increase is evident even when the overall increased rate of publica-tion is considered. We identify several current research themes, including the increasing use of pylogenetic data for interpreting the evolution of reproductive systems. Though studies of reproductive biology and of systematics have the potential for “reciprocal illumination”, few have used reproductive biological data for understanding the functional significance of morphology. Other fundamental areas where the combination of reproductive biology and systematics has proven valuable include studies of the nature of species, adaptation, speciation and hybridization. These elements of reproductive biology, especially in the context of systematic studies, will benefit from more comprehensive analyses within genera, and of taxa within communities through time and space.